2016
DOI: 10.3390/su8090833
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Consumer’s Awareness about Organic Food Products in the United Arab Emirates

Abstract: Awareness about negative externalities generated by conventional farming is gaining momentum with consumers around the world, opting for alternatively, namely organically, produced food products. Information about consumers' awareness is an essential element for farmers and marketing agencies to successfully plan production that can capture a greater market share. This study discusses effective factors influencing consumers' awareness about the benefits of organic food in the United Arab Emirates. Sample data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 20 publications
1
31
0
1
Order By: Relevance
“…Organic food is important for healthy generations. The consumption of this type of food is growing steadily in developed markets (Muhummad, Fathelrahman, & Ullah, 2016) and becoming a trend in emerging markets (Truong et al., 2012). Organic food purchase intention and behaviour have been studied for long by researchers (Rana & Paul, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic food is important for healthy generations. The consumption of this type of food is growing steadily in developed markets (Muhummad, Fathelrahman, & Ullah, 2016) and becoming a trend in emerging markets (Truong et al., 2012). Organic food purchase intention and behaviour have been studied for long by researchers (Rana & Paul, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Awareness (or consumer knowledge) of the organic food refers to the understanding of consumers on product characteristics exploration and recognition (Muhummad et al., 2016). In Vietnam, organic buying consumers faced the problem of lack of knowledge of organic food.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Another study from the consumer side explained that organic farming is a new method to avoid the costs which have been associated with conventional farming and it is considered to have ecology and environment benefits as a whole. Still, the benefits of organic farming are not well known, it will take more time and effort to make organic farming to reach in the center for farmers and consumers [41].…”
Section: Reducing Farmers' Suicides By Organic Farmingmentioning
confidence: 99%
“…In United Arab Emirates, findings indicated that men are more aware of organic products than women [55]. However, research conducted in Indonesia yielded results which indicated that gender fosters different attitudes towards organic products, women being more preoccupied by health and environmental issues than men [32].…”
Section: Literature Reviewmentioning
confidence: 99%